Local Wisdom-Based Communication for Sustainable Development : Case Study of Micro-Hydro Power Plant Planning in Kalisonggo, Pendoworejo Village, Girimulyo District, Kulon Progo Regency - Rejeki, MC Ninik Sri; Pranata, Adrianus Yoga (ENVIBILITY: Journal of Environmental and Sustainability Studies, 2024)
The research focuses on communication based on local wisdom for sustainable development, with a case study on the planning of a Micro Hydro Power Plant (MHPP) in Kalisonggo Hamlet, Pendoworejo Village, Girimulyo Sub-district, Kulon Progo Regency. The purpose of this study is to explain how local wisdom needs to be considered for sustainable development. The method used is a case study. Primary data collection was conducted through interviews and with an appreciative inquiry approach. This data is supported by secondary data. The conceptual framework used includes the ecological ethics of Kohei Saito, pre-capitalism in Asia by J. H. Boeke, and the inter- and transdisciplinary approach to sustainability communication. The research found that communication in the pre-initiation phase of MHPP development did not show the involvement of social experts and the community in the feasibility study activities to provide input, guidance, and information about local wisdom. Yet, the MHPP program being planned will be handed over to the community for management. Besides not ensuring the sustainability of a program, development that is not based on local wisdom impacts the marginalization of environmental ecosystem issues. The conclusion drawn is that communication based on local wisdom for sustainable development is a communication strategy to obtain comprehensive information about customs, traditions, social systems, and culture. Moreover, this strategy also expands and deepens efforts to involve various experts in an interdisciplinary manner and communities that have mastery of local wisdom. Therefore, the author recommends the need for an inter- and transdisciplinary approach in the planning activities of the MHPP development project and an understanding of communal-oriented ecological ethics for sustainable development. Keywords communication; local wisdom; sustainable development; inter and trans disciplinary